Comparing the merits of word writing and retrieval practice for L2 vocabulary learning. (April 2020) - Candry, Sarah; Decloedt, Julie; Eyckmans, June
Abstract: Previous research has indicated that in the case of contextual word learning, repeatedly writing a word down, i.e. engaging in a structural elaboration activity, results in better knowledge of both word form and word meaning than engaging in a semantic elaboration activity. Focusing on word form and word meaning at the same time may be an even more efficient strategy for acquiring L2 word form and word meaning, and creating form-meaning mappings. Therefore, the present decontextualized word-learning study contrasted word writing with retrieval practice, which prompts the learners to process both the form and meaning of a new L2 item in the same learning activity. 179 native Dutch-speaking EFL-learners acquired fifteen English words in one of three conditions: a word writing condition, a retrieval practice condition and a control condition in which the participants looked at the English-Dutch word pairs. Form and meaning recall tests were administered immediately after the learning procedure and one week later in order to gauge the participants' knowledge of the target vocabulary. The results indicate that retrieval practice results in better immediate and delayed form recall than both word writing and the control condition.